Primary thyroid lymphoma- case series of patients from a developing country - Sajjad Ali Khan; Dania Ali; Abdul Aziz; Najmul Islam (Journal of the Pakistan Medical Association, 2022)
Primary Thyroid Lymphoma (PTL) is a rare disease, mostly affecting middle-to-old aged females. It has a strong association with pre-existing thyroiditis, which increases the risk of its development. The disease has been studied in detail in the Western populations. However, there is lack of data for south Asians, especially in Pakistani population. This study was carried out to learn more about the disease characteristics in our area. This was a retrospective study where we reviewed four diagnosed and/or treated cases of primary thyroid Lymphoma at tertiary care hospital of Pakistan (Aga Khan University Hospital), Karachi, Pakistan. Each patient’s medical record was reviewed and studied. The participants’ average age was 62.8 ± 10.12, with two males and two females. The histology of all of the patients was compatible with the Diffuse B cell Lymphoma subtype. —Continue